Global China and Symbolic Power: The Case of 16 + 1 Cooperation. Issue 113 (3rd September 2018) - Vangeli, Anastas
Abstract: This article analyzes the practice and effects of China's new foreign policy by applying a research framework inspired by Bourdieu(s)ian international political sociology centered on the notion of symbolic power. To analyze China's symbolic power in action, the article uses the case of the cooperation between China and the 16 countries of Central, East, and Southeast Europe, dubbed '16 + 1'. It discusses how, through symbolic domination that rests on concealing the true meaning of the cooperation, China contributes to changes in the established notions on boundaries, historical legacies, and development paradigms in the region of Central and Eastern Europe (CEE).